2018
DOI: 10.1002/2017wr021563
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “An Efficient and Stable Hydrodynamic Model With Novel Source Term Discretization Schemes for Overland Flow and Flood Simulations” by Xilin Xia et al.

Abstract: Xia et al. (2017) proposed a novel, fully implicit method for the discretization of the bed friction terms for solving the shallow‐water equations. The friction terms contain h−7∕3 (h denotes water depth), which may be extremely large, introducing machine error when h approaches zero. To address this problem, Xia et al. (2017) introduces auxiliary variables (their equations (37) and (38)) so that h−4∕3 rather than h−7∕3 is calculated and solves a transformed equation (their equation (39)). The introduced auxil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The alternative method by Lu et al (2017) For all of the simulations, the numerical errors predicted by SRM are smaller than those resulting from HR except for the slightly bigger SRM L 1 error for the 1 m simulation. Particularly, the SRM L 1 and L 2 errors, which reflect the overall solution accuracy, are all much smaller than the corresponding HR errors on coarser grids (10 and 100 m).…”
Section: Key Pointsmentioning
confidence: 86%
See 3 more Smart Citations
“…The alternative method by Lu et al (2017) For all of the simulations, the numerical errors predicted by SRM are smaller than those resulting from HR except for the slightly bigger SRM L 1 error for the 1 m simulation. Particularly, the SRM L 1 and L 2 errors, which reflect the overall solution accuracy, are all much smaller than the corresponding HR errors on coarser grids (10 and 100 m).…”
Section: Key Pointsmentioning
confidence: 86%
“…This document addresses the comments raised by Lu et al (2017). Lu et al (2017) proposed an alternative numerical treatment for implementing the fully implicit friction discretization in Xia et al (2017). The method by Lu et al (2017) is also effective, but not necessarily easier to implement or more efficient.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…A face value reconstruction algorithm may affect a numerical scheme to correctly predict stationary flow at rest (e.g., C-property [1]), as well as to determine quantitative accuracy and model robustness in capturing spatially large gradients. It is found that a singlevalued definition of bed elevation at the cell-interfaces is convenient and of vital importance in devising a C-property satisfying numerical scheme [2][3][4][5]. In solving the 1LSWEs, the hydrostatic-reconstruction method (HRM) proposed by Audusse et al [3] is widely adopted; in this method, singlevalued inter-cell bed elevations are dynamically calculated based on the reconstructed inter-cell water surface elevation and water depth values.…”
Section: Introductionmentioning
confidence: 99%